The impact of standardized protocol implementation for surgical damage control and temporary abdominal closure after emergent laparotomy. Issue 4 (April 2019) - Loftus, Tyler J.; Efron, Philip A.; Bala, Trina M.; Rosenthal, Martin D.; Croft, Chasen A.; Walters, Michael S.; Smith, R. Stephen; Moore, Frederick A.; Mohr, Alicia M.; Brakenridge, Scott C.
Abstract : BACKGROUND: To standardize care and promote early fascial closure among patients undergoing emergent laparotomy and temporary abdominal closure (TAC), we developed a protocol addressing patient selection, operative technique, resuscitation strategies, and critical care provisions. We hypothesized that primary fascial closure rates would increase following protocol implementation with no difference in complication rates. STUDY DESIGN: We performed a retrospective cohort analysis of 138 adult trauma and emergency general surgery patients who underwent emergent laparotomy and TAC, comparing protocol patients (n = 60) to recent historic controls (n = 78) who would have met protocol inclusion criteria. The protocol includes low-volume 3% hypertonic saline resuscitation, judicious wound vacuum fluid replacement, and early relaparotomy with sequential fascial closure. Demographics, baseline characteristics, illness severity, resuscitation course, operative management, and outcomes were compared. The primary outcome was fascial closure. RESULTS: Baseline characteristics, including age, American Society of Anesthesiologists class, and postoperative lactate levels, were similar between groups. Within 48 hours of initial laparotomy and TAC, protocol patients received significantly lower total intravenous fluid resuscitation volumes (9.7 vs. 11.4 L, p = 0.044) and exhibited higher serum osmolarity (303 vs. 293 mOsm/kg, p = 0.001). The interval between abdominal operations was significantly shorter following protocol implementation (28.2 vs. 32.2 hours, p = 0.027). The incidence of primary fascial closure was significantly higher in the protocol group (93% vs. 81%, p = 0.045, number needed to treat = 8.3). Complication rates were similar between groups. CONCLUSIONS: Protocol implementation was associated with lower crystalloid resuscitation volumes, a transient hyperosmolar state, shorter intervals between operations, and higher fascial closure rates with no difference in complications. LEVEL OF EVIDENCE: Therapeutic study, level IV. Abstract : Supplemental digital content is available in the text.